Cerebral palsy, cesarean sections, and electronic fetal monitoring: All the light we cannot see. (September 2019) - Sartwelle, Thomas P; Johnston, James C; Arda, Berna; Zebenigus, Mehila
A half century ago electronic fetal monitoring was rushed into clinical use with the promise that the secrets of fetal heart rate decelerations had been discovered and that the newly discovered knowledge would prevent cerebral palsy with just in time cesarean sections (C-sections) preventing babies from experiencing asphyxia, which was thought to be the primary cause of cerebral palsy. In the years since electronic fetal monitoring's debut, it has been discovered that asphyxia is a rare cause of cerebral palsy. At the same time electronic fetal monitoring use increased to 85% of all labors, the C-section rate increased to 33% without an attributable decrease in the rate of cerebral palsy. What went wrong with electronic fetal monitoring? The answer lies in a new analysis of the physiologic theories concerning fetal heart rate decelerations, demonstrating that the earlier electronic fetal monitoring theories were wrong. This revelation is only the latest evidence that electronic fetal monitoring use today is harming mothers and babies with useless C-sections. Yet electronic fetal monitoring use continues unabated. Why? This article explores the complex answers and bioethical concerns, through a review of the new evidence underlying fetal heart rate decelerations in labor.